PENINGKATAN HASIL BELAJAR TEMA 5 MUATAN MATEMATIKA MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS I SDN 01 TALAWI MUDIK - Mudrianis Mudrianis (JURNAL MANAJEMEN PENDIDIKAN, 2020)
Based on the learning outcomes of Class I students of SDN 01 Talawi Mudik Theme 5 Mathematics Content it was found that the learning outcomes of Theme 5 Mathematics Content students were still incomplete. The purpose of this study was to describe and obtain information about improving student learning outcomes Theme 5 Mathematics content through the Learning Model Instant Assessment with Media Choose Number in Class I SDN 01 Talawi Mudik. This research is a Classroom Action Research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 30 students of Class I SDN 01 Talawi Mudik. Research data were collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been presented, it can be concluded that the learning model of Instant Assessment Learning Model with the media choose number can improve student learning outcomes Theme 5 Mathematics content in Class I SDN 01 Talawi Mudik. Student learning outcomes in the first cycle was 67.67% increased to 78.67 with an increase of 11%.